Transforming Biodiversity Governance - Visseren-Hamakers, Ingrid J.; Kok, Marcel T. J. (Physical Sciences, 2022)
This book outlines a governance approach that prioritizes ecocentric, compassionate and sustainable development, and stresses the importance of addressing the underlying causes of biodiversity loss. It is ideal for academics, policy makers and practitioners. This title is also available as Open Access on Cambridge Core.